Death Matters Cultural Sociology of Mortal Life - Holmberg, Tora; Jonsson, Annika; Palm, Fredrik (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book investigates death and mortality through a cultural sociological lens. The concept of death tends to remain constantly at the edge of our consciousness, intruding on our everyday experiences and practices. Death Matters is a significant contribution to death studies, going beyond traditional parameters of the field by addressing the cultural omnipresence of death. The contributions analyses several death-related meaning-making processes, arguing that meanings emerging from culturally shared narratives, social institutions, and material conditions, are just as important as 'death practices' in understanding the role of death in society. Drawing on the related themes of places of absence and presence, disease and bodies, and persons and non-persons, the authors explore a variety of areas of social life, from haunting to celebrity deaths, to move the notion of death from the margins of social reality to ongoing everyday life. This far-reaching socio-cultural collection will be of use to scholars and students across death studies, sociology, anthropology, philosophy, culture, media and communication studies. .